Design and optimization of crashworthy components based on lattice structure configuration. (August 2020) - Nasrullah, Alvian Iqbal Hanif; Santosa, Sigit Puji; Dirgantara, Tatacipta
Abstract: Designing crashworthy components requires a special structural configuration that provides effective crushing deformation to absorb crash impact energy. Recent developments in crash impact energy absorption for crashworthy components include thin wall structures, honeycomb structures, and metallic foam sandwich structures. The honeycomb and metallic foam structures appear to have high specific energy absorption capability. However, both structural configurations have a shortcoming, i.e. honeycomb structures only have the unidirectional capability, while the metallic foam structures have highly irregular (random) three-dimensional cell configuration. The advanced development of additive manufacturing has paved the way for the developments of complicated geometry that will support the development of crashworthy components in the form of lattice structures. The lattice structures provide both three-dimensional and regular structural configurations that are able to absorb crash impact energy efficiently. Therefore, lattice structures have excellent potential to be used for energy management of crash impact structures. Eleven types of lattice configurations were examined to determine the highest specific energy absorption capability, i.e. kagome, tetrahedron, pyramid, cube, truncated-pyramid, octahedron, rhombicuboctahedron, rhombic dodecahedron, open-cell, and octet lattice structures. Numerical analysis and design optimization were performed on a single cell unit of each lattice configuration. It was found that the optimum lattice configuration for crashworthy components was the octet lattice structure. Further topology optimization of the octet lattice configuration resulted in an optimum solution of the octet structure in the form of a twisted octet lattice structure. The twisted lattice structure with 20% relative density was able to generate the highest specific energy absorption. A case study on an aircraft subfloor surface structures showed that the twisted lattice structure was able to absorb aircraft grounding impact energy efficiently. General buckling failure in the twisted lattice structure can be avoided by using a tapered configuration. This tapered lattice structure has a high potential to provide specific energy absorption of up to 127 kJ/kg. These results show the potential applicability of the lattice structure for aircraft crashworthy components.